Solve the equation: `sqrt(5p+5)=sqrt(6p+1)` Topic: Math 1 Answer | Add Yours justaguide | College Teacher | (Level 2) Distinguished Educator Posted on May 21, 2013 at 1:40 AM The equation `sqrt(5p+5)=sqrt(6p+1)` has to be solved for p. `sqrt(5p+5)=sqrt(6p+1)` => 5p + 5 = 6p + 1 => 6p - 5p = 5 - 1 => p = 4 The solution of the equation is p = 4 The equation `sqrt(5p+5)=sqrt(6p+1)` has to be solved for p. `sqrt(5p+5)=sqrt(6p+1)` => 5p + 5 = 6p + 1 => 6p - 5p = 5 - 1 => p = 4 The solution of the equation is p = 4 We’ve answered 301,288 questions. We can answer yours, too. Ask a question

justaguide | College Teacher | (Level 2) Distinguished Educator Posted on May 21, 2013 at 1:40 AM The equation `sqrt(5p+5)=sqrt(6p+1)` has to be solved for p. `sqrt(5p+5)=sqrt(6p+1)` => 5p + 5 = 6p + 1 => 6p - 5p = 5 - 1 => p = 4 The solution of the equation is p = 4 The equation `sqrt(5p+5)=sqrt(6p+1)` has to be solved for p. `sqrt(5p+5)=sqrt(6p+1)` => 5p + 5 = 6p + 1 => 6p - 5p = 5 - 1 => p = 4 The solution of the equation is p = 4